Emerging Ethical Challenges in Critical Care for the 21st Century: A Case-Based Discussion - Lee, Jisoo; Ward, Nicholas S. (Seminars in Respiratory and Critical Care Medicine, 2019)
Ethical challenges for doctors and other health care professionals have existed since the practice of medicine began. Many of the oldest challenges live on to this day, such as who has more authority to make key decisions (autonomy vs. paternalism) and what are the boundaries of life at the beginning and at the end. Two powerful driving forces are new technologies and an ever-changing culture and society. The practice of medicine in intensive care units (ICUs) has been the source of many ethical challenges. Once firmly fixed concepts, such as death or “brain death” are now coming under increasing debate. In other areas, the concept of patient autonomy has been used to request life-prolonging therapies, once thought “futile.” New technologies for procreation have necessitated new ethical challenges as well. In this paper, we will use a series of cases, based on experiences from our hospital ethics committee, that occurred over the course of several years and illustrate ethical challenges which are either new to us or not new but growing in frequency due to technological or societal changes. Each one of these topics is complex and worthy of its own large review but for this overview, we will briefly discuss the key points of each dilemma.
Keywords: intensive care units; patient autonomy; futile care; medical ethics; brain death; advance directive; complementary and alternative medicine